The Global Wordsworth : Romanticism Out of Place - Bergren, Katherine (Book collections on Project MUSE., 2019)
"The Global Wordsworth examines Anglophone writers who repurposed William Wordsworth's poetry. By reading Wordsworth in dialog with South African novelist J.M. Coetzee, American abolitionist Lydia Maria Child, and Antiguan essayist Jamaica Kincaid, the book revitalizes our understanding of Wordsworth's career and its place in the canon. Wordsworth lived at a time when it was becoming possible for an English writer to be read around the world, and more than any of his contemporaries in the Romantic era, he came to be a widely read and global figure. Yet he has always seemed the most provincial of the great Romantics, even as the period's nascent globalism has become a focus of Romantic scholarship since the 1990s. This study argues that Wordsworth's afterlives in former British colonies reveal a poet whose entire career, from youth to old age, has a legible and meaningful shape; a poet who, as he aged, came to see and represent the local, the national, and the global not as separate spheres, but as entangled by forces of British imperialism and colonial expansion"--